The Impact of Edutourism "Kampung Inggris" on the Improvement of Community Welfare in South Tetebatu Village, Lombok, Indonesia - Suriani Suriani; Emilia Fatriani (Jurnal Pariwisata Nusantara (JUWITA), 2022)
Purpose: This Research aims to determine the contribution of English Village educational tourism to the level of welfare of the people of South Tetebatu. Methods: The method in this study uses qualitative methods with a case study approach. Primary research data comes from the Tetebatu Selatan Village Government and Staff, as well as the Tetebatu Selatan Village Community using interview, observation and documentation methods. Data analysis techniques using data reduction, data display and drawing conclusions. While the validity of the data using the extension of the presence of researchers and triangulation of sources. Result: The results of this study indicate that the English Village of South Tetebatu has had a positive impact on the economy and the level of welfare of the people of South Tetebatu which is marked with 1). Hotels and inns for residents close to Kampung Inggris are starting to be filled by course participants for places to stay, 2). The stretching of UMKM has also started to show results, with the presence of several small traders in the English Village area, and the spread of the laundry business, 3). Opening new job vacancies, namely providing opportunities for local people to become tutors, and other businesses such as laundry and catering certainly require employees for their operations, 4). increase the income of the local community, which has implications for the level of community welfare. In addition to the positive impact, the existence of Kampung Inggris also has a negative impact, namely the occurrence of social conflict due to the uneven distribution of beneficiaries from the Kampung Inggris Tetebatu Selatan edutour, as well as conflicts of interest between tourism development, schools and the community, by taking over part of the school land for the construction of Rest Areas and Pertashops . Contribution: this reseach is practically to be useful as input from stakeholders in South Tetebatu Village in improving the welfare of local communities with the development of tourist villages. The development of community-based tourist villages that prioritize community participant in the development of tourism Village is very necessary to improve the welfare of local communities and can reduce conflicts.